High clinical diagnostic accuracy of combined salivary gland and myocardial metaiodobenzylguanidine scintigraphy in the diagnosis of Parkinson’s disease - Li, Shuangfang; Yue, Lei; Chen, Shuzhen; Wu, Zhuang; Zhang, Jingxing; Hong, Ronghua; Xie, Ludi; Peng, Kangwen; Wang, Chenghong; Lin, Ao; Jin, Lingjing; Guan, Qiang (Frontiers in Aging Neuroscience, 2023)
Background: Decreased myocardial uptake of 131I-metaiodobenzylguanidine (MIBG) is known to be an important feature to diagnose Parkinson’s disease (PD). However, the diagnosis accuracy of myocardial MIBG scintigraphy alone is often unsatisfying. Recent studies have found that the MIBG uptake of the major salivary glands was reduced in PD patients as well. Purpose: To evaluate the diagnostic value of major salivary gland MIBG scintigraphy in PD, and explore the potential role of myocardial MIBG scintigraphy combined with salivary gland MIBG scintigraphy in distinguishing PD from non-PD (NPD). Methods: Thirty-seven subjects were performed with 131I-MIBG scintigraphy. They were classified into the PD group (N=18) and the NPD group (N=19), based on clinical diagnostic criteria, DAT PET and 18F-FDG PET imaging findings. Images of salivary glands and myocardium were outlined to calculated the MIBG uptake ratios. Results: The combination of left parotid and left submandibular gland early images had a good performance in distinguishing PD from NPD, with sensitivity, specificity, and accuracy of 50.00%, 94.74%, and 72.37% respectively. Combining the major salivary gland and myocardial scintigraphy results in the early period showed a good diagnostic value with AUC, sensitivity and specificity of 0.877, 77.78% and 94.74% respectively. Meanwhile, in the delayed period yield an excellent diagnostic value with AUC, sensitivity and specificity of 0.904, 88.89% and 84.21% respectively. Conclusion: 131I-MIBG salivary gland scintigraphy assisted in the diagnosis and differential diagnosis of PD. The combination of major salivary gland and myocardial 131I-MIBG scintigraphy further increased the accuracy of PD diagnosis.